The Effects of Kenya's 'Smarter' Input Subsidy Programme on Smallholder Behaviour and Incomes: Do Different Quasi‐experimental Approaches Lead to the Same Conclusions?. (12th April 2016) - Mason, Nicole M.; Wineman, Ayala; Kirimi, Lilian; Mather, David
Abstract: Kenya joined the ranks of sub‐Saharan African (SSA) countries implementing targeted input subsidy programmes (ISPs) for inorganic fertiliser and improved seed in 2007 with the establishment of the National Accelerated Agricultural Inputs Access Programme (NAAIAP). Although several features of NAAIAP were 'smarter' than other ISPs in the region, some aspects were less 'smart'. However, the efficacy of the programme, and the relationship between its design and effectiveness, have been little studied. This article uses nationwide survey data to estimate the effects of NAAIAP participation on Kenyan smallholders' cropping patterns, incomes, and poverty status. Unlike most previous studies of ISPs, a range of panel data‐ and propensity score‐based methods are used to estimate the effects of NAAIAP. The article then compares these estimated effects across estimators and to the effects of other ISPs in SSA, and discusses the likely links between differences in programme designs and impacts. The results are robust to the choice of estimator and suggest that, despite substantial crowding out of commercial fertiliser demand, NAAIAP had sizeable impacts on maize production and poverty severity. NAAIAP's success in targeting resource‐poor farmers and implementation through vouchers redeemable at private agro‐dealer shops likely contributed to its more favorable impacts than those of ISPs in Malawi and Zambia.